1950
DOI: 10.1017/s0025315400056186
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation in weight and chemical composition of the common British Laminariaceae

Abstract: The seasonal variations in the total ash, crude proteins, mannitol, laminarin and alginic acid contents are given for monthly samples of the Laminariaceae,L. cloustoni, L. digitataandL. saccharinafrom November 1946 to October 1948, samples ofL. digitataandL. saccharinahaving been taken at different localities to determine the effect, if any, of the degree of exposure on the chemical composition.The results agree favourably with those of the first 2 years examined and indicate that, with only a few exceptions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
142
2
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 33 publications
17
142
2
1
Order By: Relevance
“…The mannitol maximum precedes the laminaran maximum, possibly because these are interconvertible (Bidwell, 1967) and laminaran is the final storage product (Percival & McDowell, 1967). The entrained carbohydrate cycle resembled the seasonal pattern of mannitol and laminaran levels reported by Black (1948Black ( , 1951 and Haug & Jensen (1954) for field-collected L. hyperborea sporophytes. In the present investigation, maximum levels of carbohydrates were measured approximately 4 weeks before the formation of the new blade generation and were followed by a decrease in storage carbohydrate levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The mannitol maximum precedes the laminaran maximum, possibly because these are interconvertible (Bidwell, 1967) and laminaran is the final storage product (Percival & McDowell, 1967). The entrained carbohydrate cycle resembled the seasonal pattern of mannitol and laminaran levels reported by Black (1948Black ( , 1951 and Haug & Jensen (1954) for field-collected L. hyperborea sporophytes. In the present investigation, maximum levels of carbohydrates were measured approximately 4 weeks before the formation of the new blade generation and were followed by a decrease in storage carbohydrate levels.…”
Section: Discussionsupporting
confidence: 79%
“…Some metabolic enzymes (K~ppers & Weidner, 1980) and light-independent CO2-fixation of L. hyperborea (Willenbrink et al, 1975) were reported to oscillate seasonally. The classic publications of Black (1948Black ( , 1951 and Haug & Jensen (1954) showed marked seasonal changes of biochemical compounds such as storage carbohydrates, alginic acid and protein in field-collected material of various Laminaria species. The ecological strategy of Laminaria species, which store carbohydrates in summer and later remobilise them to support growth in winter (Schmitz et al, 1972;L/ining et aI., 1973), requires a close coupling of biochemical compounds and the growth rhythm.…”
Section: Introductionmentioning
confidence: 98%
“…Another possibility is that there is a seasonal fluctuation in some features of the habitat to which the inversion polymorphism is responding. There are certainly variations in temperature, humidity and salinity of seaweed deposits, and seasonal changes in several chemical constituents of seaweeds (e.g., mannitol, alginic acid, laminarin) have been described (Black, 1948(Black, , 1951a lb-see also the review by Chapman and Chapman, 1980). Whatever the cause of the apparent fluctuations in inversion frequencies, the finding that it is consistent in widely spaced populations is compelling evidence for the action of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate materials not only constitute between 10 and 40 wt% of the dry weight of many common kelps [22], but they are also largely responsible for the metal sequestering properties of brown macroalgae (figure 1) [36]. Thus, studies of discrete metal alginate salts can be used to model macroalgal thermal degradation, exemplifying the effects of a particular metal ion on pyrolysis without the results being convoluted by processes related to the decomposition of other compounds in the rest of the biomass.…”
Section: Introductionmentioning
confidence: 99%